Bone Bruise of the Thoracic Spine Caused by Mild Physical Activity in Children - Kenji Yokoyama; Kenji Endo; Yoichiro Takata; Fumitake Tezuka; Hiroaki Manabe; Kazuta Yamashita; Toshinori Sakai; Takashi Chikawa; Akihiro Nagamachi; Koichi Sairyo (Case Reports in Orthopedics)
Vertebral bone bruise (VBB) in children commonly occurs following a fall from a height, and more than one vertebral body may be affected. We encountered 6 children each with a single VBB caused by mild physical activity. All the children had tenderness on the corresponding spinous process with no neurologic findings. Magnetic resonance imaging (MRI) showed typical findings of VBB in all cases. The children were treated conservatively with a soft thoracolumbar brace and instructed to rest with no physical activity for a month. At follow-up 1 month later, the back pain had diminished, and the signal changes seen on MRI had disappeared in all cases. We conclude that mild physical activity may be a cause of VBB in children and good clinical results can be achieved by using a soft thoracolumbar brace and rest.